Influence of brand name on consumer decision making among UiTM Malacca City Campus students: ‘a study on international fast food industry’ / Julaiha Mohammad Marzuki and Nur Hidayah Syasya Zamri - Mohammad Marzuki, Julaiha; Zamri, Nur Hidayah Syasya (Faculty of Business and Management, 2016)
Fast food restaurant represent one of the largest segments of food industry with over 200,000 restaurants and $120 billion in sales in the US alone. In Malaysia, consumers prefer to order fast food due to its convenience and fast serving of foods. As consumers are becoming more careful about daily meal spending and under high stress and pressures in urban cities, they tend to order value set lunch and set dinners when they are dining out. The purpose of this research is to investigate the influence of brand name on consumer decision making with the factor of brand loyalty, brand awareness, and perceived quality. Furthermore, researchers also going to identify which factor the most significant factor that influenced the consumer decision making on purchasing fast food. This research used primary data majorly in collecting the data where the researchers distribute the questionnaire to the respondents. The interpretation of the data used correlation coefficient for testing the hypothesis, while using regression analysis for testing the most significant variables in this research. Based on our findings, the factors of brand loyalty, brand awareness, and perceived quality overall have positive correlation with the consumer decision making. The factor brand loyalty shows the most significant factors in influencing consumer decision making.